Characterization of composite materials using full field data - Syed Muhammad, Kashif (IIUM Press, 2011)
Characterization of anisotropic materials and particularly composite materials requires great number of experiments for a complete characterization and identification of all the directional constitutive properties. Lately due to the technological advancements in optical measurements and computational resources, new methods have been proposed based on full field data measured on the surface of a test specimen. On one hand a good quality optical device is required to capture the image of the specimen, whereas on the other hand, sufficient computational resource is required to exploit the rich data captured by a high resolution digital camera. This chapter discusses the issues related to the use of such full filed data for the characterization of composite or complete anisotropic materials.